PERAN ORANG TUA DALAM PENDIDIKAN KARAKTER ANAK DI LINGKUNGAN KELUARGA - Siti Rahmatina; Nena Puspita Sari; Afrida Hanum; Musfirah Musfirah; Nursaimah Nursaimah (COVIT (Community Service of Health), 2022)
Family is the first place a child gets education. Instilling character in children is not only the responsibility of the teacher which is obtained through formal education, but parents as real caregivers will have a greater responsibility in building character. Various controversies are faced by parents of students in playing the role of teacher, especially in educating children to grow to have good character. The purpose of this service is to socialize the importance of the role of parents in children's character education. The approach method used is individual and group. In the discussion that was going on, a number of complaints from participants who were also educators at home during Covid-19, of course, got good solutions through exposure to material and previous research, as well as discussions and questions and answers. Through the results of this service it is concluded that the character education that must be fostered in the family environment is (1) Religious character values, (2) Discipline character values, (3) Creative character values, (4) Independent character values, (5) Responsibility character values, and (6) Curiosity character value. These character values ??must be developed in order to bring big changes. The success or failure of the development of character values ??in children is highly dependent on the cooperation between teachers and parents as role models for children. Keywords: Role of Parents, Character Education